Review of the monograph “Linguistic tuning forks of meaning” by V.I. Karasik (Moscow: Pushkin State Institute of the Russian Language, 2024. 416 p.) - Vorkachev, Sergey G. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The monograph is devoted to the issues of linguaculturology, linguasemiotics and discourse studies. It consists of four thematic sections: linguaconceptology, narratology, discourse science and the section devoted to the study of the axiological properties of nominations. Comprehension of linguacultural concepts is carried out on the basis of existence forms – peaceful life and competition, natural and artifactual objects – desert, swamp, train station and bazaar, as well as atmospheric and biological phenomena – fog and blood. The narratology issues are studied on the basis of the allegorical interpretation of the plots of Russian, Armenian and Kalmyk fairy tales, fairy tales of the Bantu peoples, the axiology of anime, fairy, the axiology of life and death in a poetic text. The properties of discourse are considered through its symbolic, fascinative, desiderative and optative, destructive and comic characteristics, as well as through the evaluative specificity of pedagogical and educational discourses. The nomination properties are studied in terms of communicative restrictions and taboos, gender asymmetry of pejorative vocabulary, asymmetry of partial quality and characteristics of low-quality artifacts. The monograph is meant for philologists and a wide range of researchers developing the fundamentals of an integral human science.